Penerapan Metode Joint Application Design (JAD) dalam Pengembangan Sistem Informasi Penjualan Jaket Hoodie Berbasis Website - Aldisa, Rima Tamara; Alfarisi, Sechan; Furqon, Muhammad (STMIK Budi Darma, 2022)
An effective sales system in a company requires an innovation and novelty in building a system that can help companies reach all market segments and society. Because the company's business activities still apply offline sales methods, namely coming directly to the store, viewing products and paying in cash. To meet the needs of the company and its customers, this company requires a web-based or online system for sales and customer data storage purposes. The programming language used is the PHP language using the CodeIgniter framework and MySQL as the database. The results of the research and the results of the output of this system will produce a website-based information system for selling jackets or clothes that can be used by the company or jacket shop to meet the needs of selling Hoodie Jackets from every consumer quickly and accurately, and is expected to assist in perform category searches by size, product orders, and digital payments for products.Â